De-escalation of immunomodulator and biological therapy in inflammatory bowel disease. (January 2020) - Chapman, Thomas P; Gomes, Catarina Frias; Louis, Edouard; Colombel, Jean-Frédéric; Satsangi, Jack
Summary: Treatment strategies for inflammatory bowel disease (IBD) focus on the induction and long-term maintenance of deep remission to avoid complications of active disease and improve long-term outcomes. Medical therapies for IBD, notably the increasingly widespread use of biological therapy, are often effective at controlling disease, but these drugs are associated with substantial adverse events, which together with other factors—including increasing treatment costs and patient preferences—leads to concerns regarding indefinite use of medical therapy. Consequently, the need to consider the safety and feasibility of drug de-escalation once IBD remission has been achieved is clear. Here, we review the current evidence surrounding de-escalation of immunomodulator and biological therapy in Crohn's disease and ulcerative colitis. We discuss strategies for de-escalation, including the selection of patients who are appropriate for treatment de-escalation and the use of proactive drug monitoring, and review the evidence on subsequent optimal follow-up. We conclude by proposing an algorithm to guide de-escalation decisions, and highlight future perspectives, including the potential effect of emerging medication and personalised medicine for these diseases.